Effects of Liquid Smoke Concentrations on The Characteristics of Smoked Cuttelfish - Indah Widiastuti; Herpandi Herpandi; Muhammad Ridho; Nafa Ya’la Arrahmi (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Cuttlefish is a seasonal and highly perishable fishery commodity. Accordingly, processing is needed to increase the shelf life of the cuttlefish. Fish smoking using liquid smoke has been widely used for processing. This study was aimed to determine the effect of liquid smoke concentration on the quality of smoked cuttlefish product. Four liquid smoke concentrations (0%, 6%, 12%, and 18%) were compared and the product quality was evaluated based on the chemical properties and sensory evaluation. The results showed that liquid smoke significantly affected the moisture and phenol content but the ash, protein, lipid and cholesterol content were not different. The different in liquid smoke concentration also did not significantly affect the sensory properties of the smoked cuttlefish. The chemical analysis revealed the polyunsaturated fatty acids were dominant in the smoked cuttlefish as compared to the monounsaturated fatty acids and the saturated fatty acids (34.4% vs 22.7% vs, 27.0%, respectively)